2022
DOI: 10.3917/reof.173.0117
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity, convergence and imbalances in the Euro area

Abstract: The inception of the euro allowed countries from the periphery to experience a large fall in the cost of borrowing. Lower nominal rates were only partially offset by lower inflation rates. We rationalize this real interest rate reversal using a two-region model of a monetary union where, consistently with real interest rate data, discount factors are initially heterogeneous, leading the periphery to be borrowing-constrained. We model the inception of the euro as a partial convergence process in inflation rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…This enabled some member states to have higher than average inflation rates continuously. Auray and Eyquem (2021) showed that partial inflation convergence, together with the common monetary policy and the ECB interest rate created a large positive demand shock in peripheral countries, creating pressure on the relative prices of goods and services produced there. The boom in consumption and investment led to current account deficits.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This enabled some member states to have higher than average inflation rates continuously. Auray and Eyquem (2021) showed that partial inflation convergence, together with the common monetary policy and the ECB interest rate created a large positive demand shock in peripheral countries, creating pressure on the relative prices of goods and services produced there. The boom in consumption and investment led to current account deficits.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Given the heterogeneity of EU's Member States (GNP, infrastructure, agricultural productivity, rate of new technologies integration etc.) (Auray and Eyquem, 2021;Reimer et al, 2023;Triantafyllidis et al, 2023;Petrović et al, 2024), the heterogeneity of agricultural structures across the Union (Kryszak and Herzfeld, 2021), and the farmers' heterogeneous attitudes towards sustainability related policies (Niskanen et al, 2021) the Commission should provide a wide range of alternatives that lead to that desired outcome. In an effort to address the farmers protests across the EU and de-escalate the rising tension, von der Leyen announced in 2024 the withdrawal of the Sustainable Use Regulation (Euronews, 2024b).…”
Section: Holistic Approach Of Agricultural "Sustainability"mentioning
confidence: 99%
“…Auray & Eyquem [3] showed that there was significant convergence of inflation rates among countries that formed EMU in 1999, when comparing average inflation rates in the period before financial crisis and before the advent of Monetary union. However, that convergence was not finished in later stages, leading to significant differences in real interest rates.…”
Section: Literature Reviewmentioning
confidence: 99%